Respostas
respondido por:
4
Resposta:
x = -1
Explicação passo-a-passo:
6(x+4)=8-2(2x-3)
6x + 24 = 8 - 4x + 6
6x + 24 = 14 - 4x
6x + 4x = 14 - 24
10x = -10
x = -10/10
x = -1
Prova real:
6(x+4)=8-2(2x-3)
6(-1+4)=8-2(2.-1-3)
6.3 = 8-2(-2-3)
18 = 8-2.-5
18 = 8+10
18 = 18
brendasousaoliveira:
obrigada
respondido por:
1
Resposta:
x = -1
Explicação passo-a-passo:
Exercício de equação primeiro grau:
6(x+4)=8-2(2x-3)
6x+24= 8-4x+6
6x+4x= 14-24
10x= -10
X = -10/10
x= -1
Perguntas similares
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás